2014
DOI: 10.1038/ejhg.2014.123
|View full text |Cite
|
Sign up to set email alerts
|

Phenome-wide association studies (PheWASs) for functional variants

Abstract: The genome-wide association study (GWAS) is a powerful approach for studying the genetic complexities of human disease. Unfortunately, GWASs often fail to identify clinically significant associations and describing function can be a challenge. GWAS is a phenotype-to-genotype approach. It is now possible to conduct a converse genotype-to-phenotype approach using extensive electronic medical records to define a phenome. This approach associates a single genetic variant with many phenotypes across the phenome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The majority of PheWAS studies have used data from de-identified Electronic Health Records [9,11,17,2028] (EHRs) linked to genotype data, while a few have been performed in large-scale epidemiologic studies[2932] and clinical trials[33,34]. The representation of the phenome varies in each of these types of studies.…”
Section: Phenotype Data In Phewasmentioning
confidence: 99%
“…The majority of PheWAS studies have used data from de-identified Electronic Health Records [9,11,17,2028] (EHRs) linked to genotype data, while a few have been performed in large-scale epidemiologic studies[2932] and clinical trials[33,34]. The representation of the phenome varies in each of these types of studies.…”
Section: Phenotype Data In Phewasmentioning
confidence: 99%
“…Using public repositories of evidence for SNP functionality can provide a way to focus on SNPs more likely to impact phenotype. One PheWAS within the Marshfield PMRP used 105 presumed functional stop-gain and stop-loss variants, and identified a nonsense variant in ARMS2 associated with age-related macular degeneration [12]. In another PheWAS from the eMERGE network, Verma et al[37], used multiple sources of information to identify 25 SNPs known or highly likely to be stop-gain inducing variants.…”
Section: Electronic Health Record Based Phewasmentioning
confidence: 99%
“…PheWAS began with investigation of the association between multiple SNPs and de-identified electronic health record (EHR) data [5], and has now been used successfully several times with EHR data [612]. Since then, PheWAS has been used with epidemiological study data and clinical trials data [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings from studies of pharmacogenomics and the newly-developed pharmacoproteomics [3] and pharmacometabolomics [4] have revealed pervasive effects of genetic polymorphisms on drug efficacy or toxicity, not only urging for personalized drug treatments according to individual patient's genetic characteristics but also adding more layers of complexity to the combination of multi-drug regimen [4] . Furthermore, the current definition of clinical phenotypes of disease (eg, hypertension, heart failure, type-2 diabetes, etc) and related drug therapy has shown serious limitations that conceal the ever-increasing details of genomic variants discovered by the genome-wide association studies (GWAs) [5] . Clearly, newer approaches are needed for Western medicine to refine the symptoms-or evidence-based definition Editorial of disease and drug responses so that the intrinsic complexity of the disease, the outcomes of drug treatment, and the impact of multiple environmental factors can be unequivocally characterized and classified.…”
mentioning
confidence: 99%